PUREE PURPLE SUBSTITUTION IN WINGKO PRODUCT DEVELOPMENT - Nismara Cetta Rosyiidah; Minta Harsana (Journal of Applied Culinary Arts, 2025)
The objectives of this final project are (1) To find the right recipe for Wingko products with purple sweet potato puree substitution; (2) Determine the packaging of Wingko products with the addition of purple yam; (3) To find out the level of public preference for Wingko with purple sweet potato substitution; (4) Measuring the composition of information on the nutritional value of Wingko products with purple sweet potato substitution; (5) Measuring the selling price of BEP Wingko with purple sweet potato substitution. This type of research uses an R&D development method with a 4D (Define, Design, Developer, and Disseminate) development model: (1) At the define stage, there is one reference recipe selected from the three existing reference recipes, the assessment is carried out by 3 lecturers and 3 recipes are selected; (2) The design stage begins by designing a formulation with purple sweet potato puree substitution materials with a percentage of 25%, 35%, and 50%, then a sensory test is carried out with 5 panelists: 2 lecturers and 30 female food students and gets the highest average on formula 2 (35%); (3) The development stage is a trial stage carried out by 3 expert lecturers, at this stage a validation process is carried out which can be carried out as a stage of product improvement. The validation results state that the development product is acceptable and can be continued. After the validation process was carried out, it was then continued with a sensory test with 30 semi-trained panelists, namely food students and got the results that there was no difference between the reference product and the development product; (4) The disseminate stage was carried out with sensory tests of 60 panelists, namely participants of the Bhojana Boga culinary festival. The results of this study show that: (1) the right recipe for Wingu products is the development of Wingko with the addition of 35% purple yam; (2) The product is packaged using rice paper complete with logo, headline, subheadline; (3) public acceptance of Wingko products on average in terms of aroma, color, taste, texture; (4) analyzing the nutritional content of Wingko protein products 2.70%, fat 2.59%, carbohydrates 1.59%, moisture content 45.29%, ash content 1.02%; (5) The selling price of the product is Rp.12,000 with a break even point of 103 units.